Tindakan Sosial Pada Lirik Lagu Album Hurje ! Maka Merapallah Zarathustra Karya Pangalo Kajian Sosiologi Sastra - Serly Lutfi Setiyawan; Harjito Harjito; Nazla Maharani Umaya (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to determine the form of social action in the song lyrics on the album Hurje! Maka Merapallah Zarathustra by Pangalo!, using qualitative descriptive methods and content analysis. The analysis was carried out based on a literary sociology approach with the help of social action theory to find out how social action takes shape in the lyrics of the album Hurje! Maka Merapallah Zarathustra. The theory of social action used in this research is based on Max Weber's opinion about forms of social action consisting of instrumental rational action, value-oriented rational action, traditional action, and affective action. The results of this research show that in the song lyrics on the album Hurje! Maka Merapallah Zarathustra by Pangalo!, there are various forms of social action which include instrumental rational action, value-oriented rational action, traditional action, and affective action. It was concluded that there were 81 social actions. These various social actions were found based on the analysis of 62 instrumental rational actions, 8 value-oriented rational actions, 5 traditional actions, and 6 affective actions..